Cognitive Disorders Associated with Different Operations (Eurasian Research Bulletin, 2023)
The term postoperative cognitive impairment was introduced to denote cognitive impairment that develops early (72 hours after surgery) and persists into the late postoperative period. Currently, the term POCD refers to the impairment of one or more cognitive functions, which is assessed using a series of neuropsychological tests performed before and after surgery.